2010
DOI: 10.1002/cncr.24925
|View full text |Cite
|
Sign up to set email alerts
|

Weekly docetaxel, cisplatin, and 5‐fluorouracil as initial therapy for patients with advanced gastric and esophageal cancer

Abstract: BACKGROUND: Docetaxel, cisplatin, and 5-flurouracil (DCF) administered every 3 weeks produces a high rate of treatment-related adverse events. The objective of the current study was to evaluate the efficacy and tolerability of a weekly formulation of DCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 51 publications
3
49
1
3
Order By: Relevance
“…Weekly administration decreased the rate of hematological toxicity, with only 4 % of grade 3-4 neutropenia [16]. However, nonhematologic toxicities were frequent with this regimen, with 23 % of patients hospitalized for non-hematologic toxicity in this retrospective study by Overman et al In a phase II trial reported by Tebbut et al [17], with weekly mDCF there was a high rate of grade 3-4 gastrointestinal toxicity (diarrhea 22 %, stomatitis 18 %, nausea 16 %, asthenia 18 %) as reported earlier by Lorenzen et al [18], who noted a similar toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…Weekly administration decreased the rate of hematological toxicity, with only 4 % of grade 3-4 neutropenia [16]. However, nonhematologic toxicities were frequent with this regimen, with 23 % of patients hospitalized for non-hematologic toxicity in this retrospective study by Overman et al In a phase II trial reported by Tebbut et al [17], with weekly mDCF there was a high rate of grade 3-4 gastrointestinal toxicity (diarrhea 22 %, stomatitis 18 %, nausea 16 %, asthenia 18 %) as reported earlier by Lorenzen et al [18], who noted a similar toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…The V325 prompted a series of investigations aimed at improving the tolerability of DCF with modified schemes, envisioning the use of weekly schedules. Overman et al [18] retrospectively evaluated data from 95 patients treated with weekly DCF, reporting a dramatic drop in the rate of hematological toxicity and modest activity. Nevertheless, hospitalization was required for 22 patients (23 %) because of nonhematological toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…The pretreatment characteristics of patients are listed in Table 1. None of the patients had previously received chemotherapy for advanced disease; 9 patients had received adjuvant chemotherapy without docetaxel or oxaliplatin with a median disease-free interval of 12 months (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Figs. 1, 2).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Currently, many other studies that tested the different DCF regimens have been published [37][38][39][40][41][42][43][44][45]. The standard DCF regimen used by Van Cutsem et al was a 5-day regimen.…”
Section: Discussionmentioning
confidence: 99%